The 2nd International Online-Conference on Nanomaterials 2020
DOI: 10.3390/iocn2020-07793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Fullerenol Derivative for Potential Biological Applications

Abstract: Several biological barriers are generally responsible for the limited delivery of cargoes at the cellular level. Fullerenols have unique structural features and possess suitable properties for interaction with the cells. This study aimed to synthesize and characterize a fullerenol derivative with desirable characteristics (size, charge, functionality) to develop cell penetration vehicles. Fullerenol was synthesized from fullerene (C60) solubilized in toluene, followed by hydroxylation with hydrogen peroxide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…In the as-synthesized fullerenol, the two peaks observed at 2,963 and 2,873 cm –1 (C-H st ) were attributed to residual TBAH ( Kokubo et al, 2011 ). Purified fullerenol showed a broad band at around 3,424 cm –1 (O-H st ) and four characteristic bands at 1,598 cm –1 (C=C st ), 1,410 cm –1 (O-H b ), 1,352 cm –1 (C-O-H b ), and 1,112 cm –1 (C-O st ), which agree well with previously reported data ( Kokubo et al, 2011 ; Ravelo-Nieto et al, 2020 ). Silanization was confirmed by the presence of new bands at 2,964 cm –1 (C-H st as ), 2,934 cm –1 (C-H st sy ), 2,875 cm –1 (H-C (-N) st ), 1,564 cm –1 (N-H b ), and 1,344 cm –1 (C-N st ), which can be attributed to propylamine groups.…”
Section: Resultssupporting
confidence: 92%
“…In the as-synthesized fullerenol, the two peaks observed at 2,963 and 2,873 cm –1 (C-H st ) were attributed to residual TBAH ( Kokubo et al, 2011 ). Purified fullerenol showed a broad band at around 3,424 cm –1 (O-H st ) and four characteristic bands at 1,598 cm –1 (C=C st ), 1,410 cm –1 (O-H b ), 1,352 cm –1 (C-O-H b ), and 1,112 cm –1 (C-O st ), which agree well with previously reported data ( Kokubo et al, 2011 ; Ravelo-Nieto et al, 2020 ). Silanization was confirmed by the presence of new bands at 2,964 cm –1 (C-H st as ), 2,934 cm –1 (C-H st sy ), 2,875 cm –1 (H-C (-N) st ), 1,564 cm –1 (N-H b ), and 1,344 cm –1 (C-N st ), which can be attributed to propylamine groups.…”
Section: Resultssupporting
confidence: 92%
“…Studies have shown improved performance associated with the application of NPs delivery mechanisms, and some of these drugs have been approved by the FDA and are already part of antineoplastic clinical practice, including the drugs doxorubicin, cisplatin, paclitaxel, vincristine, and cyclodextrin. The most commonly used nanomaterials in these nanoformulations are liposomes, dendrimers, CNTs, inorganic NPs, micelles, magnetic NPs, and CQDs [ 18 , 92 , 93 , 112 , 151 ].…”
Section: Discussion and Perspectives On The Use Of Aloe Ver...mentioning
confidence: 99%
“…In addition, fullerenol synthesized from fullerene (C60) represents a promising candidate for the carrier effect as a “molecular chassis”, due to the enhanced cellular uptake and endosomal escape compared to other conventional polymeric vehicles. In this context, fullerenes possess unique structural features and properties suitable for cell–cell interactions, which are essential for biological and biomedical applications and depend on features such as size, charge, and functionalization, due to their efficient interactions with biomolecules [ 93 ].…”
Section: Carbon-based Nanomaterials With Antitumor Activitiesmentioning
confidence: 99%
See 2 more Smart Citations